76 INSIDE VEIN GRAFT FAILURE: A WORK FOR OCT. (15th December 2022) - Bendandi, Francesco; Ciurlanti, Leonardo; Chietera, Francesco; Mazzapicchi, Alessandro; Foroni, Marco
Abstract: An 84-years-old woman with prior history of triple coronary artery bypass graft and subsequent percutaneous coronary intervention (PCI) of saphenous vein graft (SVG) for right coronary artery (RCA) was admitted for non-ST-elevation myocardial infarction and newly diagnosed atrial fibrillation. Coronary angiography showed chronic occlusion of native vessels and good flow in all grafts, in absence of critical stenoses. However, SVG for RCA presented a small filling defect of non-univocal interpretation (atherothrombosis, thromboembolus, venous valve). Optical coherence tomography (OCT) was performed for better assessment of the lesion, which was found to be a red thrombus, overlying a ruptured thin-cap fibroatheroma. To reduce the risk of distal embolization, a well-known complication of SVG PCI, direct stenting with conservative stent sizing was performed: everolimus-eluting stent diameter (3, 5 mm) was chosen according to mean reference lumen diameter, while length (18 mm) was determined to obtain complete plaque coverage. Repeated OCT showed proximal stent malapposition and underexpansion at the mid portion. The stent was post-dilated with 4, 0×12 mm non-compliant balloon and final OCT showed correction of both malapposition and underexpansion. The presented case offers an example of the advantages of intravascular imaging in diagnosis and treatment of SVG lesions. Venous grafts have high failure rate: up to 12% of graft are occluded before hospital discharge and up to 60% after 10 years. While in the first year graft occlusion is mainly caused by neointimal hyperplasia, after this period neoatherosclerosis is the leading cause of failure, as exemplified in the case. Intravascular imaging, and particularly OCT, may help to elucidate graft failure mechanism, with important implications for treatment strategy. Moreover, SVG interventions have higher incidence procedural complications, particularly no-reflow and periprocedural myocardial infarction, due to high plaque burden and friable atheromatous material. Proposed strategies to mitigate procedural risk include use of embolic protection devices, direct stenting and use of undersized stents. In this complex setting, intravascular imaging can guide stent sizing and optimization, thus reducing procedural complications and long-term lesion failure.